Indian Agent Involvement in the Establishment of Permanent Settlement for the South Indian Labouring Community, 1923-1941 - M. Utaman Raman; Sivachandralingam Sundara Raja (Kajian Malaysia, 2021)
This article investigates a long-neglected aspect of Indian Malaysian history, namely the Indian Agents of the Government of India to British Malaya. The Indian Agents were representatives of the Indian Government who were appointed under the Indian Immigration Act of 1922 to investigate and report on the state of affairs of Indian communities in the British colonies. The official duties of the Indian Agents in British Malaya were formalised under Section 73 (III) of the Labour Code 1923. Between 1923 and 1941, six Indian Agents were appointed in British Malaya. Throughout their tenure, they focused on and reported extensively on the socioeconomic conditions of the Indian working-class community, particularly south Indian labourers. One problem that came to their attention was the underdevelopment of the community’s permanent settlement in the country. The Federated Malay States (FMS) government did not appear to be concerned about the situation. Similarly, private estate managers reacted indifferently to the issue. Both saw permanent settlement as simply an economic measure to keep the community as a labour force, rather than a way to alleviate their socioeconomic hardships. This article shows how the Indian Agents were able to uncover a range of issues that were impeding the establishment of permanent settlements for south Indian labourers in the FMS. Some of them demonstrated exceptional levels of direct involvement. The article’s primary goal is to assess the degree to which the Indian Agents influenced the overall development of permanent Indian labour settlement.